THE METHODS OF TEACHING FOLKORE WORKS AT SCHOOLS - Uzakova Saltanat Paraxatovna (American Journals, 2022)
The samples of teaching methods are taught in this article. During the lessons, a type of lessons and teaching mathods have been successful in literary education and students have obtained some knowledge and concepts through learning the theme.
Keywords: literary education, lesson process, lesson, lesson plan, lesson content, lesson type, teaching methods, quality text.